2020
DOI: 10.1002/jlb.3mr0420-067r
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of surface molecules on extracellular vesicles in cancer, autoimmune diseases, and coagulopathy

Abstract: Extracellular vesicles (EVs) are nanosized particles that have emerged as mediators for intercellular communication in physiologic and pathologic conditions. EVs carry signaling information on their bilipid membrane as well as cargo within, allowing them to perform a wide range of biologic processes and contribute to pathophysiologic roles in a wide range of diseases, including cancer, autoimmune diseases and coagulopathy. This review will specifically address the function of surface molecules on EVs under nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Cardiovascular diseases (CVDs) are caused primarily by atherosclerosis, a chronic inflammatory disease in which the vascular endothelium is constantly damaged, causing endothelial dysfunction [ 41 , 42 ]. EVs of various cells such as leukocytes, platelets, smooth muscle cells and endothelial cells are involved in all stages of vascular inflammation, including endothelial activation, monocyte adhesion and transmigration, resulting in atherosclerosis [ 9 , 43 , 44 ]. Indeed, it has been reported that EVs can induce the release of pro-inflammatory cytokines, such as interleukin (IL)-6 and IL-8, from endothelial cells or leukocytes [ 45 , 46 ].…”
Section: The Role and Therapeutics Potential Of Extracellular Vesicles In Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) are caused primarily by atherosclerosis, a chronic inflammatory disease in which the vascular endothelium is constantly damaged, causing endothelial dysfunction [ 41 , 42 ]. EVs of various cells such as leukocytes, platelets, smooth muscle cells and endothelial cells are involved in all stages of vascular inflammation, including endothelial activation, monocyte adhesion and transmigration, resulting in atherosclerosis [ 9 , 43 , 44 ]. Indeed, it has been reported that EVs can induce the release of pro-inflammatory cytokines, such as interleukin (IL)-6 and IL-8, from endothelial cells or leukocytes [ 45 , 46 ].…”
Section: The Role and Therapeutics Potential Of Extracellular Vesicles In Inflammatory Diseasesmentioning
confidence: 99%
“…EVs have been reported to have a variety of functions and, in particular, contribute to antigen-specific and non-specific immune regulation to both immune and non-immune cells in the form of immunomodulation [ 7 , 8 ]. They also likely play an important role in modulating inflammatory diseases, such as cardiovascular disease, dermatitis, diabetes, and arthritis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the increasing number of new cases of autoimmune diseases and the poor understanding of the etiologies of autoimmune diseases that greatly impedes the prevention, diagnosis and treatment of autoimmune diseases, researchers worldwide have been searching for more reliable and convenient biomarkers for autoimmune diseases. Some previous studies have determined that EVs are involved in immunostimulation or immunosuppression in autoimmune diseases through pro-inflammatory or anti-inflammatory effects induced by their specific constituents [10,14,15,19,20]. Moreover, studies have suggested increasing total EVs levels and specific EVs constituents as potential diagnostic biomarkers in several autoimmune diseases, such as primary Sjögren's syndrome, systemic lupus erythematosus, and systemic sclerosis [21] (Fig.…”
Section: Evs As Potential Biomarkers In Autoimmune Diseasesmentioning
confidence: 99%
“…Proven to increase adhesion molecule expressions, chemokine productions, and structural alterations in macrovascular and microvascular endothelial cells, which can lead to endothelial alterations and tissue leukocyte infiltration [10,33], MPs in the plasma of SLE patients have been intensively studied as elements in "liquid biopsies" for SLE (Table 2).…”
Section: Evs In Systemic Lupus Erythematosusmentioning
confidence: 99%
See 1 more Smart Citation